Whole genome sequencing for metastatic mutational burden in extraskeletal myxoid chondrosarcoma - Zou, Trudy; Sethi, Rahil; Wang, Jiefei; Budak, Gungor; Chandran, Uma; John, Ivy; Watters, Rebecca; Weiss, Kurt (Frontiers in Molecular Medicine, 2023)
Extraskeletal myxoid chondrosarcoma (EMC) is an ultra-rare cancer that makes up less than 3% of all soft tissue sarcomas. It most often arises in the soft tissues of the proximal limbs and has a higher incidence in males. Though EMC has a good prognosis, it has an indolent course with high rates of local recurrence as well as metastasis to the lungs. EMC is characterized in 70% of cases by an EWS1-NR4A3 translocation, leading to constitutive expression of NR4A3. Structural variants (SVs) in EMC, especially large-scale genomic alterations, have not been well studied and studies are severely limited by sample size. In this study, we describe Whole Genome Sequencing (WGS) of a rare case of matched EMC primary tumor, lung metastasis, and pelvic metastasis to identify genomic alterations. We examined somatic variants, copy number variants (CNVs), and larger scale SVs such as translocations and breakend points. While the primary tumor and lung metastasis had similar somatic variations and CNVs, the pelvic metastasis had more unique SVs with especially increased mutational burden of SVs in chromosome 2. This suggests that different molecular drivers appear in more advanced, relapsing EMC compared with the primary tumor and early lung metastasis. Genomic studies such as ours may identify novel molecular complexities in rare cancers that may be leveraged for therapeutic strategies and precision medicine.